1994
DOI: 10.1152/jappl.1994.76.5.2119
|View full text |Cite
|
Sign up to set email alerts
|

Changes in magnetic resonance images of muscle depend on exercise intensity and duration, not work

Abstract: Echo-planar magnetic resonance imaging was used to study the effect of exercise rate and duration on magnetic resonance imaging signal intensity (SI) of anterior tibialis muscle in normal human subjects (mean age 35 yr, n = 6). Axial midcalf echo-planar images (repetition time/echo time = 6,000/45, acquisition time = 80 ms) were acquired every 6 s for 1 min before and during 15 min of dynamic ankle dorsiflexion exercise (peak force 36% of 1 repetition maximum) at 10, 20, and 30 contractions/min. At each rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
94
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 0 publications
8
94
1
1
Order By: Relevance
“…Jenner et al (14) reported an approximately exponential rise in SI during isotonic dorsiflexion exercise. Others (2,19) have shown a more complex pattern to the SI changes during and after exercise, with (sometimes) an abrupt initial rise, a dip (possibly below baseline), a secondary rise, and continued increases after exercise.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Jenner et al (14) reported an approximately exponential rise in SI during isotonic dorsiflexion exercise. Others (2,19) have shown a more complex pattern to the SI changes during and after exercise, with (sometimes) an abrupt initial rise, a dip (possibly below baseline), a secondary rise, and continued increases after exercise.…”
mentioning
confidence: 99%
“…Any of these possible explanations, acting alone or in concert with the others, suggests that the intracellular T2 increase results from changes in the chemical behavior of water resulting from increased flux through energy metabolism pathways. In keeping with the long time required for flux through these pathways to reach a steady rate (ϳ2-3 min), these changes make up a slowly evolving, large-magnitude component of the mfMRI response (14).Changes in the extracellular space also affect the SI in mfMRI. Increases in interstitial volume [such as those caused by exercise (24) or leg negative pressure (18)] increase SI in T2-weighted images (6, 18), although the low interstitial volume fraction diminishes the importance of these changes (4, 18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas magnetic resonance (MR) imaging (MRI) has been used to acquire anatomical information (4,5,22), use of human skeletal muscle has also been assessed with exercise-induced contrast shift in transverse relaxation time (T2) of MR images (1-3, 6, 7, 14, 21, 33-35, 42). It has been demonstrated that this contrast shift is correlated with integrated EMG activity (1), related to isometric torque induced by electromyostimulation (EMS) (2), increases with exercise intensity (1,2,21,26,30,33,36) and the metabolic state of skeletal muscle (37,40,42), and can discriminate use among relatively small synergistic muscles (13,14) and neuromuscular compartments (3). Thus exerciseinduced contrast shift in MR images seemed ideal to assess neuromuscular plasticity among synergists.…”
mentioning
confidence: 99%